A review of dengue virus and its vectors (Research, Society and Development, 2021)
The first reports of a disease with similar clinical prognoses in humans to dengue are reported in the Chinese Medical Encyclopedia of the Jin Dynasty (265-420 AD). The disease is endemic in countries in Africa, the Americas, Asia, the Caribbean and the Pacific. Dengue is considered a re-emerging viral disease, with an estimated nearly 400 million new dengue infections per year worldwide. Currently, dengue affects billions of people who live in areas at risk of infection with clinical manifestations such as fever, rash, eye pain and hemorrhage. Dengue is a matter of sanitary and environmental concern in many countries around the world, particularly in tropical and subtropical countries where the vector mosquitoes Aedes aegypti and Aedes albopictus are present in the environment of these locations. The transmission of this virus in humans, known as horizontal transmission, occurs through the bite of infected females of one or the other of the two species of mosquitoes. In this article, a bibliographical research was carried out to understand and analyze the object of study in scientific articles and technical standards. The characterization of dengue transmission and symptoms is of paramount importance for the ideal implementation of new control and prevention programs for public policies in society, including control campaigns in society. Providing descriptions that can help combat dengue transmission and prepare for outbreak response and allow early detection of notifications and timely responses in areas of dengue incidence.